Myanmar Monthly Food Price Report – July 2025 - Htar, May Thet; Minten, Bart; Masias, Ian (International Food Policy Research Institute, 2025)
KEY HIGHLIGHTS: Rice prices in July 2025 declined nationally, falling by 6 percent year-on-year and 1 percent compared to last month. However, notable price increases were observed in the past month in Kachin (+9 percent), due to road closures, and Kayin (+9 percent), due to flooding. Export crop prices diverged, with green gram and maize increasing this year due to strong international demand, while black gram and pigeon pea declined year-on-year due to reduced demand in India. Animal-sourced food prices surged over the last year, led by pork (up 67 percent), due to rising production and fuel costs, while fish prices rose amid strong export demand. Fish prices increased in July compared to the previous month, driven by bad weather that prevented many offshore fishing vessels from operating. Multiple risks lie ahead, including falling international rice prices, ongoing conflict, and natural hazards, all of which may undermine agricultural production, farm income, and food security.